1992
DOI: 10.1104/pp.99.3.1169
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Diterpene Biosynthesis in Rice (Oryza sativa L.) by Chitin

Abstract: Cell-free extracts of UV-irradiated rice (Oryza sativa L.) leaves have a much greater capacity for the synthesis from geranylgeranyl pyrophosphate of diterpene hydrocarbons, including the putative precursors of rice phytoalexins, than extracts of unstressed leaves (KA Wickham, CA West [1992] Arch Biochem Biophys 293: 320-332). An elicitor bioassay was developed on the basis of these observations in which 6-day-old rice cell suspension cultures were incubated for 40 hours with the substance to be tested, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 34 publications
2
62
0
2
Order By: Relevance
“…The results described in this paper clearly demonstrated that the N-acetylchitooligosaccharides of certain size are highly potent biotic elicitors for rice cells and can elicit the production of phytoalexins of biologically significant level. Our results coincide with those obtained by Ren and West 13 ) who showed that one of the enzymes proposed for the biosynthetic pathway of these phytoalexins could also be elicited by chitin. One of the most active oligo saccharides in our experiments, N-acetylchitoheptaose, could elicit the production of a detectable amount of momilactone A from 10-9 to 10-6 M (1 ng-l fJ,gjml).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results described in this paper clearly demonstrated that the N-acetylchitooligosaccharides of certain size are highly potent biotic elicitors for rice cells and can elicit the production of phytoalexins of biologically significant level. Our results coincide with those obtained by Ren and West 13 ) who showed that one of the enzymes proposed for the biosynthetic pathway of these phytoalexins could also be elicited by chitin. One of the most active oligo saccharides in our experiments, N-acetylchitoheptaose, could elicit the production of a detectable amount of momilactone A from 10-9 to 10-6 M (1 ng-l fJ,gjml).…”
Section: Discussionsupporting
confidence: 82%
“…Nishizawa and Hibi 12 ) also reported the induction of mRNA coding a chitinase in cultured rice cells by glycol chitin. Very recently, Ren and West 13 ) reported that chitin could induce diterpene hydrocarbon synthase, one of the enzymes proposed for the biosynthetic pathway of diterpenoid phytoalexins, in suspension-cultured rice cells. They did not show, however, the precise information on the size and structure of t To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…lignification in wheat leaves (Barber et al, 1989), chitinase activity in melon (Roby et al, 1987), and β-1,3 glucanase gene expression in cultured barley cells (Kaku et al, 1997). In cultured rice cells, chitin oligosaccharides induced phytoalexin synthesis (Ren and West, 1992;Yamada et al, 1993), generation of reactive oxygen species (Kuchitsu et al, 1995), biosynthesis of jasmonic acid (Nojiri et al, 1996), and expression of defence related genes (Minami et al, 1996;Nishizawa et al, 1999;Takai et al, 2001). A possible explanation for the high levels of protection observed in our study may therefore be that (Lamb et al, 1989).…”
Section: Discussionmentioning
confidence: 66%
“…These reactions include the following: ion flux variations, cytoplasmic acidification, membrane depolarisation and protein phosphorylation (Felix et al 1993, 1998), chitinase and glucanase activation (Roby et al 1987; Tayeh et al 2015), lignification (Kawasaki et al 2006; Ali et al 2014), generation of reactive oxygen species (ROS) (Kuchitsu et al 1995), biosynthesis of jasmonic acid (JA) (Nojiri et al 1996), and phytoalexins (Ren and West 1992; Yamada et al 1993), and the expression of early responsive and defence-related genes (Minami et al 1996; Libault et al 2007). Moreover, chitosan induces proteinase inhibitors (Walker-Simmons and Ryan 1984), phytoalexin biosynthesis (Hadwiger and Beckman 1980) and callose formation (Köhle et al 1985) in dicot species.…”
Section: Introductionmentioning
confidence: 99%